The Investigation of Figurative Language in “The Count of Monte Cristo” Movie - Ramadhan, Muhammad Rayhan; Ambalegin, Ambalegin (eScience Humanity Journal, 2024)
This research aimed to investigate the use of figurative language in “The Count of Monte Cristo” movie. In this research, qualitative descriptive used as the research method. The researchers examined the script from “The Count of Monte Cristo” movie as the data source. In collecting the data, the method was observation and the technique was non-participant. Meanwhile, in analyzing the data, the method was identification and the technique was matching to the theory. The utterances from the transcript of the movie which were taken as the data were analyzed narratively. The researchers used the theory of (Abrams & Harpham, 2013) to discover the use of figurative language. The researchers discovered 22 utterances from the movie’s script that show the use of figurative language. There were simile, metaphor, hyperbole, and personification.